2022
DOI: 10.3390/toxins14120830
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Catalase Supplementation Alleviates Deoxynivalenol-Induced Oxidative Stress and Gut Microbiota Dysbiosis in Broiler Chickens

Abstract: Catalase (CAT) can eliminate oxygen radicals, but it is unclear whether exogenous CAT can protect chickens against deoxynivalenol (DON)-induced oxidative stress. This study aimed to investigate the effects of supplemental CAT on antioxidant property and gut microbiota in DON-exposed broilers. A total of 144 one-day-old Lingnan yellow-feathered male broilers were randomly divided into three groups (six replicates/group): control, DON group, and DON + CAT (DONC) group. The control and DON group received a diet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Solid lipid nanoparticles based on phosphatidylcholine stabilizers, is a functional CAT supplement designed to resist enteric digestion and deliver potent antioxidant activity 575 . Supplemental CAT is shown to alleviate OxS in the GI tract and improve gut microbiota 576 . Lactic acid bacteria, Lactobacillus casei BL23, L. delbrueckii subsp.…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…Solid lipid nanoparticles based on phosphatidylcholine stabilizers, is a functional CAT supplement designed to resist enteric digestion and deliver potent antioxidant activity 575 . Supplemental CAT is shown to alleviate OxS in the GI tract and improve gut microbiota 576 . Lactic acid bacteria, Lactobacillus casei BL23, L. delbrueckii subsp.…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…In this study, we found similar results that TA, a natural polyphenolic compound, could also improve antioxidant capacity and modulate gut microbiota in piglets. Interestingly, our results found that the abundance of Candidatus Brocadia and Escherichia‐Shigella are negatively linked to gut antioxidant capacity, suggesting that members of these two genera may play an important role in disrupting gut redox homeostasis [54]. Thus, the decrease of these two genera in the gut by dietary TA supplementation may be one of the reasons why TA could improve gut antioxidant capacity in piglets.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, AFB 1 exposure triggers a stress response in chickens, leading to immune suppression and inflammation [ 27 ]. This weakened immune system becomes less efficient in controlling the growth of opportunistic pathogens like Proteobacteria, which can readily exploit the situation and proliferate, causing dysbacteriosis and intestinal inflammation; these are commonly associated with increased permeability and chronic systemic inflammation [ 28 ]. In the present study, poults fed with AFB 1 showed a significant increase in Proteobacteria and a significant reduction in Firmicutes.…”
Section: Discussionmentioning
confidence: 99%